State and Fate of Glaciers in the Val Veny (Mont-Blanc Range, Italy): Contribution of Optical Satellite Products - Antoine Rabatel; Etienne Ducasse; Victor Ramseyer; Romain Millan (Revue de Géographie Alpine)
The glaciers of the Val Veny (Italian side of the Mont-Blanc Massif) have been the site of numerous field observations during the last decades, in particular for the study of glacial fluctuations or surface processes related to the debris cover. Here, we propose to examine how satellite observations can complement field measurements on the state and fate of the Val Veny glaciers. Indeed, satellite products obtained in a quasi-systematic way allow to account not only for the loss of surface and volume, but also for the changes in their flow velocities. The overall pattern we document is a glacier thinning and slowdown of the ice flow, with an estimated shrinkage of 25% by 2050 and a volume loss ranging between 30 and 43% depending on the data source used for the estimation of the initial volume. In such a context, a portion of the upper reaches of Brenva Glacier shows an unexpected pattern of thickening and increase in ice flow that rises questions on its origin. Finally, the uncertainties in the estimation of ice thicknesses remain important and have repercussions on the future evolution of the glaciers and their contribution from a hydrological point of view. By 2050, we estimate that the water contribution due to the volume loss of Val Veny glaciers could decrease by 40%.